Nucleophilic Difluoroalkylation of Isocyanates with Difluoromethyl 2‐Pyridyl Sulfone. Issue 16 (12th November 2015) - Li, Shan; Peng, Peng; Wei, Jun; Hu, Yongzhou; Hu, Jinbo; Sheng, Rong
Abstract: The nucleophilic difluoroalkylation of isocyanates with difluoromethyl 2‐pyridyl sulfone furnished 2, 2‐difluoro‐2‐pyridinylsulfonylacetamides with good to excellent yield. These products can be converted to 2, 2‐difluoroacetamide sulfinate, iododifluoroacetamide and 2‐aminopyridine derivatives easily. Abstract :